2020
DOI: 10.1101/2020.05.27.20115048
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Correlation of the global spread of coronavirus disease-19 with atmospheric air temperature

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an enveloped virus that may be sensitive to heat. We assessed whether the spread of coronavirus disease 2019 (COVID-19) correlates with air temperature. We also studied whether additional climate, geographical, and population variables were correlated. The total number of confirmed COVID-19 cases and mortality rates reported in each country between 1st Jan and 31st Mar 2020 were compared with the country's three-month average atmospheric air tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Pearson correlation analysis in another study revealed that average temperature negatively correlates with the attack rate, a similar concept as the CFR in terms of infectivity (r = -0.36, p = 0.02) ( Hassan et al, 2020 ). This result is consistent with that of a study that used Spearman correlation analysis ( Bezabih et al, 2020 ).…”
Section: Introductionsupporting
confidence: 93%
“…Pearson correlation analysis in another study revealed that average temperature negatively correlates with the attack rate, a similar concept as the CFR in terms of infectivity (r = -0.36, p = 0.02) ( Hassan et al, 2020 ). This result is consistent with that of a study that used Spearman correlation analysis ( Bezabih et al, 2020 ).…”
Section: Introductionsupporting
confidence: 93%
“…The transmission rate of COVID-19 is expressed as the daily number of infections (11,25,28), or the total number of confirmed cases (7,9,12,16,23). In other studies, the number of cases accumulated over a period of time (18,20,29), average daily cumulative rate of confirmed cases (13), or cases per 100000 (27) represent COVID-19 transmission.…”
Section: Methodsmentioning
confidence: 99%
“…In some studies, the temperature is expressed as the average daily temperature (13,14,20,22,25,29), or the average temperature over a period of time (7,9,23). Others use the 14-day exponential moving averages (EMAs) of daily average temperature (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronaviruses are large, enveloped RNA viruses of both medical and veterinary importance (6). The envelope structures of SARS-CoV-2 are sensitive to physical and chemical conditions and can be destabilized or damaged by heat, ultraviolet (UV) light or extreme pH (7). The outermost structural protein of the SARS-CoV2 "Spike protein" showed active and inactive states at different temperatures (8).…”
Section: Introductionmentioning
confidence: 99%